Geographical reflections of mine pollution in Bosnia and Herzegovina and Croatia - Musa, Snježana; Šiljković, Željka; Šakić, Dario (Journal for Geography, 2017)
Numerous landmine fields cause an immense problem for the development of economy in rural areas of the Republic of Croatia and Bosnia and Herzegovina. Even twenty years after the Homeland War in Croatia, i.e. the same period after signing the Dayton Accord and war cessation in Bosnia and Herzegovina, huge areas are still contaminated with landmines. In Croatia are approximately 1.69 % of contaminated territory agricultural areas in the east part of country, forests and forestry land, i.e. pastures in highlands and the Mediterranean areas are most endangered. Bosnia and Herzegovina is one of the most landmine contaminated countries in the world.  Severe landmine contamination in Bosnia and Herzegovina has been detected on pasture and forestry land, in the vicinity of the former war zone, in the central part of the country. Out of the total number of 1,366 landmine contaminated settlements in the Bosnia and Herzegovina territory, some 1,169 are rural communities.
Keywords: mines; minefields; rural communities of Croatia and Bosnia and Herzegovina